Glucose Modulates Human Ventral Tegmental Activity in Response to Sexual Stimuli. Issue 1 (1st January 2018) - Ulrich, Martin; Stauß, Philipp; Grön, Georg
Abstract: Background: Attribution of salience to sexual stimuli is mediated by the dopaminergic midbrain, including the ventral tegmental area (VTA). The existence of glucose-sensing neurons in the VTA, as suggested by animal studies, offers the opportunity to modulate aberrant salience coding involved in sexual disorders such as sexual addiction. Recent neuroimaging work supported that VTA activity in humans can be modulated by intravenously infusing a small bolus of glucose. However, that study used appetitive food stimuli, leaving the possibility that glucose modulation of VTA-mediated salience coding might be bound to this class of stimuli. Aim: To test whether glucose-modulatory effects generalize to food-unrelated stimuli despite being in the class of primary reinforcers. Methods: During functional imaging, 37 healthy men were exposed to images showing nude or clothed female upper bodies. At the end of the 1st quarter (∼6 minutes) of the experiment, 18 participants received a small amount of intravenously infused glucose. Results: Before glucose administration, VTA activity was higher for nude than for clothed female stimuli. After infusion of glucose, this pattern reversed such that VTA activity was higher for clothed than for nude female stimuli. The effect was at its maximum approximately 7 to 12 minutes after glucose infusion, changing back during the experiment's 4th phase. In another 19 participants not treated with glucose, VTA activity was consistently higher for nude than for clothed female stimuli throughout the experiment. Conclusion: The present findings show that glucose modulates VTA-mediated salience coding of sexual stimuli. These results suggest that glucose might affect salience coding in a stimulus-general way. However, future studies are necessary to address the question of whether glucose modulation also affects the VTA's salience coding of secondary reinforcers.